Les indépendantistes vénézuéliens face à l’esclavage : les défis d’une révolution atlantique dans une société coloniale (1790-1830) - Frédéric Spillemaeker (Astérion)
From the end of the 18th century to 1830, Hispanic America entered the era of Atlantic revolutions. On the shores of Venezuela in the 1790s, the echoes of the French revolutions in Santo Domingo and other West Indian islands contributed to the flowering of revolts and conspiracies with new slogans. The demands for freedom for slaves and equality for mestizos were now part of a new horizon of revolutionary expectation. However, the Hispanic monarchy was still able to mobilise troops in defence of the established order. From 1806 onwards, the Venezuelan Francisco de Miranda, a former general in the French Revolution, tried to coordinate the efforts of the first independence fighters, although without success. The first independence was proclaimed in Caracas in 1811 within a context of dislocation of the Hispanic monarchy following the invasion of Napoleonic troops and conflicts between the Spanish and Hispanic Americans. The patriots proclaimed civil equality by putting an end to the socio-racial categories of the Ancien Regime, whilst maintaining slavery. Only gradually did they incorporate slaves into the armies in exchange for freedom. Despite these armed liberations, the alliance with Haiti and the attempts of Simón Bolívar, independence did not coincide with the abolition of slavery that was finally proclaimed in Venezuela in 1854.